2005
DOI: 10.1039/b506949a
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies of the cationic aluminium(chloro) hydroxides by quantum chemical ab initio methods

Abstract: Cationic aluminium(chloro) hydroxide complexes with two to four aluminium atoms were studied using quantum chemical methods. Complexes were studied in both gas and liquid phase. The liquid environment was modeled by using a conductor-like screening model (COSMO). COSMO calculations were carried out as a single point calculation at the optimized gas phase structures. Water (epsilon = 78.54) was used as the solvent. The minimum energy structures obtained from the gas phase studies were mostly compact cyclic stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 24 publications
5
37
0
Order By: Relevance
“…The bridging structure is supposed to be more stable than the associated structure with electrostatic force. The discussion of these structures is very important when the formation of aluminum polymers and the precipitation of aluminum ions are considered 15–17…”
Section: Resultsmentioning
confidence: 99%
“…The bridging structure is supposed to be more stable than the associated structure with electrostatic force. The discussion of these structures is very important when the formation of aluminum polymers and the precipitation of aluminum ions are considered 15–17…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, many-body interactions, including polarization, are included in a parameter free way as the simulation proceeds. For highly charged ions, it has been demonstrated that AIMD works reliably [12][13][14]21 and we will show that there is very good agreement between simulated extended x-ray absorption fine structure ͑EXAFS͒ spectra and the results of measurements.…”
Section: Introductionmentioning
confidence: 88%
“…However, it has been recently demonstrated that a QM/MM approach in which the dynamics in the QM region is treated using a fast AIMD solver ͑herein called AIMD/MM methods͒ has been shown to greatly improve performance for dynamical calculations. 12 In this study we report Zn 2+ + 64H 2 O 300 K AIMD, Zn 2+ +6H 2 O / 58H 2 O 300 K AIMD/MM, and Zn 2+ +6H 2 O / 250H 2 O 300 K AIMD/MM ͑all the first shell water molecules are AIMD and the rest are MM͒ simulations based on density functional theory ͑DFT͒. Our primary focus is on the elucidation of the transition from a highly structured and strongly polarized first solvation shell to the bulk structure of water, as well as comparisons with putative structural interpretations used to analyze various existing x-ray and neutron scattering data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, computational chemistry is introduced to determine the structures of the complexes. 43 Our group has earlier demonstrated the power of computational chemistry for investigating the structures of polymeric aluminium species. 43,44 Here, we used computational methods (DFT, MP2) based on quantum mechanics to resolve the structures of the aluminium species detected in the experimental part of the study.…”
Section: Introductionmentioning
confidence: 99%